\[\boxed{\text{1040\ (1040).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[= m\left( m^{2} - 9 \right) - \left( m^{3} - 8 \right) =\]
\[= m^{3} - 9m - m^{3} + 8 =\]
\[= 8 - 9m,\ при\ m = - \frac{2}{3}\]
\[8 - 9 \cdot \left( - \frac{2}{3} \right) = 8 + \frac{9 \cdot 2}{3} =\]
\[= 8 + 3 \cdot 2 = 8 + 6 = 14.\]
\[4 \cdot \left( \frac{3}{4} \right)^{2} - 3 \cdot \frac{8}{9} \cdot \frac{3}{4} =\]
\[= \frac{4 \cdot 9}{16} - \frac{3 \cdot 8 \cdot 3}{9 \cdot 4} = \frac{9}{4} - \frac{8}{4} = \frac{1}{4}\text{.\ }\]
\[\boxed{\text{1040.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[= \left( 4a^{2} + 3 + \left( 7 - 4a^{2} \right) \right)^{2} =\]
\[= \left( 4a^{2} + 3 + 7 - 4a^{2} \right)^{2} = 10^{2} =\]
\[= 100\]
\[100 = 100 \Longrightarrow ч.т.д.\]
\[= (a - 3b)^{2}(a + 3b)^{2} =\]
\[= \left( a^{2} - 9b^{2} \right)^{2} - \left( a^{2} - 9b^{2} \right)^{2} =\]
\[= 0\]
\[0 = 0 \Longrightarrow ч.\ т.\ д.\]